2017
DOI: 10.1139/cjfas-2016-0331
|View full text |Cite
|
Sign up to set email alerts
|

Development of a foraging model framework to reliably estimate daily food consumption by young fishes

Abstract: We developed a foraging model for young fishes that incorporates handling and digestion rate to estimate daily food consumption. Feeding trials were used to quantify functional feeding response, satiation, and gut evacuation rate. Once parameterized, the foraging model was then applied to evaluate effects of prey type, prey density, water temperature, and fish size on daily feeding rate by age-0 (19–70 mm) pallid sturgeon (Scaphirhynchus albus). Prey consumption was positively related to prey density (for fish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…Box plot distribution of the modeled 24‐h change in body weight (g) using the Fish Bioenergetics 4.0 application (Deslauriers et al. 2017a) and the Pallid Sturgeon model (Heironimus ) for each of the six length categories of age‐0 sturgeon. For more detail on box plot components and statistical interpretation see caption for Figure .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Box plot distribution of the modeled 24‐h change in body weight (g) using the Fish Bioenergetics 4.0 application (Deslauriers et al. 2017a) and the Pallid Sturgeon model (Heironimus ) for each of the six length categories of age‐0 sturgeon. For more detail on box plot components and statistical interpretation see caption for Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Using age‐0 Pallid Sturgeon (41–108 mm), Deslauriers et al. (2017b) found that gut residence time decreased exponentially over time at water temperatures of 14°C, 18°C, and 24°C, which usually resulted in low gut fullness values after 24 h. As such, the prey weight present in the gut at the time of capture likely underestimated 24‐h consumption for most individuals. Despite this, nearly 5% of the fish examined during this study exhibited modeled weight gains; this included individuals from all six length categories.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To account for fish size, we regressed prey weight with body weight in order to calculate the studentized residuals for prey weight, which were used as the dependent variable in subsequent linear regression analyses at the reach, bend, and trawl spatial scales. Laboratory diet experiments demonstrated that age‐0 pallid sturgeon (41–108 mm) usually had low‐gut fullness values after 24 hr at water temperatures of 14, 18, and 24°C (Deslauriers, Rosburg, & Chipps, ); thus, foraging habitat was calculated by averaging estimates from the day of capture and the previous day, which was then used as the independent variable. We used a Bonferroni correction (0.05/3 = 0.017) to decrease the potential for a Type 1 error from multiple foraging habitat regressions.…”
Section: Methodsmentioning
confidence: 99%